Faktor Risiko Kejadian Infeksi Cacing Tambang pada Petani Pembibitan Albasia di Kecamatan Kemiri Kabupaten Purworejo - Norra Hendarni Wijaya; Anies Anies; Suhartono Suhartono; Suharyo Hadisaputro; Henry Setyawan (Jurnal Epidemiologi Kesehatan Komunitas, 2016)
Background : The prevalence of hookworm infection in Indonesia in 2002 - 2006 amounted to 2,4% ; 0,6% ; 5,1% ; 1,6% and 1,0%. No data reports on de-worming of DHO Purworejo. The results of a preliminary study of the month January 2014 shows the proportion of de - worming of 94,1% of the population of farmers plant nursery albasia 51 people, with the proportion of 41,2% hookworm.Methods : This study is observational analytic study with cross-sectional design. The study sample as many as 101 people, with purposive sampling. Samples taken from population studies that met the inclusion criteria (job as Albasia nursery growers, willing as respondent, place of residence in the territory of the district health center Kemiri, aged 18-64 years) and criteria exclusion (habit of consumption of raw vegetables, travel/resettled in a long time, not willing to be made respondents).Results : The proportion of patients with hookworm infection (64,3 %) or 65 people. The risk factors are shown to affect the incidence of hookworm infection among others ; wash feet after work (OR = 4,41), available toilet at work (OR = 3,77), wash hands after work (OR =3,74) and wear footwear when working (OR = 3,56).Conclusion : Several risk factors that influence the incidence of hookworm infection in nursery growers in the district albasia hazelnut is to wash the feet after work, lack of latrines in the workplace, wash hands after work and do not use footwear when working with a probability of 99,03%.